Why manage a forest? - Giacomini, Ricardo Marostica; Weiser, Veridiana de Lara (Technical and Scientific Journal Green Cities, 2025)
In the current scenario of environmental degradation and climate emergency, this article discusses the importance of Sustainable Forest Management and Adaptive Forest Management as essential tools for the conservation of Brazilian ecosystems and the maintenance of biodiversity. The study presents different management models, such as the Digital Forest Exploitation Model, non-timber forest management, and community forest management. It also explores ecological restoration techniques, including the control of invasive species, the application of prescribed fire, and the use of ecological corridors. Furthermore, the article addresses gaps in legislation, emphasizing the need to update regulations to reflect scientific advancements and meet the demands for ecological restoration and sustainable exploitation of forest resources. The relevance of these practices is highlighted not only for biodiversity maintenance but also for generating social benefits, such as the subsistence of traditional communities and the promotion of essential ecosystem services.
Keywords: Biodiversity; Conservation; Sustainability